SMEs, territorial development and networking: the case of Romania - Daniela Luminita Constantin (European Regional Science Association (ERSA), 2002)
The purpose of this paper is to explore the main features and the significance of the SME sector development for approaching the regional question in Romania during the transition period and to identify the first signs and the perspectives of SME territorial networking phenomenon. It also aims at analysing the usefulness and the relevance of this concept and those directly related to it (local entrepreneurship, local milieu) for regional policy purposes. The evolution of the Romanian sector of SMEs expresses a variety of conditions and causes, the following being the most relevant: the absence of such a sector before 1990; the legal framework adopted for setting up this kind of enterprises; the incentives provided at the beginning of the process and thereafter; the speed of restructuring and privatisation of the state firms. Accordingly, the first section of the paper focuses on the actual state of SME sector in Romania: the analysis undertaken by ownership type, size and economic activity has pointed out the further development potential of SMEs, stressing the idea of a real, deeper support that needs to be offered to this sector, concentrated on three aggregate objectives: the removal of any administrative, financial, legal, etc. barriers that still hinder the SME starting-up and development; the provision of assistance and information to SMEs; encouraging co-operation and partnership between firms. The next section deals with the quantitative, qualitative and sectoral aspects of the territorial distribution of SMEs, their role in territorial development and competition. It also seeks to identify phenomena characteristic to territorial networking in which SMEs can bring a significant contribution. Finally, the third section addresses the question of SME development and networking within the overall regional policy. The main conclusion is that the Romanian SME sector can represent an important source of local and regional dynamism. Even though the big firms remain a key factor of restructuring the productive system, from regional viewpoint the SME activity appears as a strategic one for each region`s economic reconstruction, provided SMEs be included in a well-structured environment, in a coherent territorial network, involving links, relations, exchanges between them and other economic agents (like banks, higher education institutes, training centers, consulting firms, chambers of commerce, local public administration). The analysis performed in this paper reveals that the framework for networking not only at regional level but also at interregional and international level has been created but so far there is not enough information to measure the scope of this phenomenon. The extension of the process of parallel outsourcing of functions that could be better performed by specialised suppliers within indirect vertical integration through the creation of networks of local subcontractors, the creation of spin-offs and new firms in related sectors still remain subjects for further studies in this field.
Keywords: 330